Correction: del Re et al. Data from Emergency Medical Service Activities: A Novel Approach to Monitoring COVID-19 and Other Infectious Diseases. Diagnostics 2025, 15, 181 - Daniele del Re; Luigi Palla; Paolo Meridiani; Livia Soffi; Michele Tancredi Loiudice; Martina Antinozzi; Maria Sofia Cattaruzza (Diagnostics)
In the original publication [...]